HUBUNGAN PERSEPSI RISIKO DENGAN KEINGINAN SISWA DALAM MENJAGA HIGIENE MENSTRUASI DI SEKOLAH DASAR KAMONING SAMPANG - Nurul lailatul badriyah; Ira Nurmala (The Indonesian Journal of Public Health, 2019)
Maintaining menstrual hygiene is essential to avoid vulvar pruritus, irritation, swelling, vaginal secretions, reproductive tract infections, urinary tract infections, uterine cancer, etc. Sampang is the region with the highest maternal mortality rate in Madura, but recently, maternal mortality rate in Sampang continues to decline. One of the causes of maternal death is due to the lack of reproductive hygiene maintenance during menstruation, so that mothers are at risk of uterine cancer. The present study aimed to analyze the relationship between risk perception and female students’ desire in SDN Kamoning in maintaining menstrual hygiene. It was an observational analytic research using cross sectional research design. This study employed HAPA theory. Health Action Process Approach (HAPA) is a concept approach to change one's behavior by strengthening intention to become action. The variable of risk in HAPA theory can influence individual perception early in the motivation phase. The samples of the study were 32 people, and they were taken by total sampling because the number of samples was very small. Data were collected through questionnaire, and they were analyzed by using spearman correlation. The results showed that there was correlation between perception of risk (p = 0,000) and intention to maintain menstrual hygiene. Relationships obtained were not strong because some respondents did not agree with the statements in the questionnaire. It can be concluded that there is a relationship between risk perception and intention to maintain personal hygiene during menstruation. Although the relationship obtained showed a strong relationship, there were some female students that still had wrong perception about personal hygiene maintenance during menstruation.